Differentiated Learning Strategies in Social Studies: Addressing the Diversity of Student Learning Styles in the Classroom, Elementary School Students - Dwi Aprilia; Haryati, Tati (Yayasan Insan Mulia Bima, 2026)
The complexity of the social environment in everyday life makes Social Studies (IPS) a fundamental subject in elementary education. However, the presentation of conventional, uniform instruction still fails to accommodate the significant diversity in students' learning readiness, interests, and learning styles. The purpose of this study is to identify, analyze, and propose practical, evidence-based differentiated learning strategies specifically tailored for elementary Social Studies content to effectively meet students' diverse learning styles. This study uses a qualitative research method, specifically a literature review, by drawing on major pedagogical frameworks, curriculum documents, and empirical studies regarding differentiation and Social Studies instruction in Elementary School. The results of the study indicate that the successful implementation of differentiation involves utilizing three main strategic areas: 1) Differentiated Content, for example, providing multi-modality resources such as historical graphic novels and audio clips; 2) Differentiated Process (for example, establishing varied Learning Centers or Learning Stations that cater to different sensory inputs); and 3) Differentiated Product, for example, allowing students to demonstrate mastery through visual mapping, oral presentations, or hands-on simulations. The research findings confirm that the application of these differentiated strategies significantly enhances student engagement, sharpens critical thinking skills, and results in a more comprehensive and meaningful understanding of core Social Studies concepts at the Elementary School level